2022
DOI: 10.6007/ijarems/v11-i3/15067
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Consumer’s Behavioural Intention to Purchase Fresh Agricultural Products from In-App

Abstract: This paper presents the factors that influencing consumer on in-App purchase behaviour for fresh agriculture product. The consumer can be defined as a person or groups that buy goods for their consumption and not for resale or commercial purpose. Consumer behaviour is the study of the processes involved when individual or groups select, purchase, use, or dispose of the product, service, ideas or experiences to satisfy needs and desires. While, the in-App purchase can be referred to the buying of product, good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Green education, sometimes referred to as environmental education, is a concentrated attempt to teach people about how natural environments function and how they may control their behaviour and ecosystems in order to live sustainably. According to Ahmad et al [5], there are two ways that environmental information can be presented to consumers: either by educating them about the product's extensive environmental impacts or by informing them that it was produced in an environmentally friendly way. Shen et al [6] found that environmental danger appeals, perceived severity, and perceived authenticity of advertisements all play a part in proenvironmental behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green education, sometimes referred to as environmental education, is a concentrated attempt to teach people about how natural environments function and how they may control their behaviour and ecosystems in order to live sustainably. According to Ahmad et al [5], there are two ways that environmental information can be presented to consumers: either by educating them about the product's extensive environmental impacts or by informing them that it was produced in an environmentally friendly way. Shen et al [6] found that environmental danger appeals, perceived severity, and perceived authenticity of advertisements all play a part in proenvironmental behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of adopting a social science perspective, audience research has always emphasised enhancing the effectiveness of current commercials. According to the findings, Ahmad et al [5] stated that consumers are pragmatic, so while establishing green advertising strategies, advertisers should provide as much information about the product as they can. The authors of this study examine how consumer purchase intentions in environmental advertising are influenced by media, claim credibility, relevance, information, and perceived effectiveness of environmental behaviour.…”
Section: Introductionmentioning
confidence: 99%